Parenting styles and digital literacy: Uncovering their correlation among adolescents - Kusumalestari, Ratri Rizki; Oesman, Maya Amalia; Ahmadi, Dadi; Umar, Muthiah; Yulianita, Neni (Jurnal Kajian Komunikasi, 2023)
Background: The development process of digital literacy is gradual and significantly influenced by parenting style. How parents raise their children significantly impacts how well-trained adolescents are in media-related behaviour. Purpose: The study aims to examine the relationship between the digital literacy levels of adolescent - students at the Faculty of Communication Science, Universitas Islam Bandung - and the parenting styles they experience within their families. Methods: This research employed a quantitative approach within the positivistic paradigm. It involved a sample of 120 students. Results: This study revealed that adolescents from families with authoritative parenting styles exhibited higher levels of digital literacy than those from authoritarian, permissive and neglectful families. Meanwhile, adolescents from neglectful family backgrounds demonstrated the lowest degree of digital literacy. These findings provide a foundation for developing adolescent digital literacy and, consequently, promoting cyber wellness by achieving a balance between online and offline life. Conclusion: This research indicated no significant relationship between parenting style and students’ digital literacy at the Faculty of Communication, Universitas Islam Bandung. Implications: Nevertheless, it is worth noting that students raised within a family with an authoritative parenting style tend to exhibit higher digital literacy abilities, although the difference is not statistically significant. This study also introduces a comparative theory, highlighting the contrast between students, who are digital natives, and their parents, who can be considered digital immigrants.